Implementasi kebijakan vaksinasi covid-19 di Indonesia: narrative review - Sutari Sutari; Haerawati Idris; Misnaniarti Misnaniarti (Riset Informasi Kesehatan, 2022)
Background: Currently the Covid-19 pandemic is still happening which has resulted in an increase in the number of deaths. The number of Covid-19 cases in Indonesia is more than 2.5 million with the death toll reaching 25,000. To prevent the transmission of Covid-19, the government has made a policy with a vaccination program. Methods: The research method used is narrative review, searching for articles using an internet database with the keywords COVID-19 vaccination in Indonesia with a time limit of 2020 to 2021. The search results obtained 10 articles which were then analyzed using context, input, process and product (CIPP) on the implementation of the Covid-19 vaccination. The obtained literatures were synthesized using the narrative method by grouping the extracted data that was similar to the measured results to answer the research objectives. Results : The results of the study indicate that the existence of a policy and the government's pick-up effort is expected to support the success of vaccination. However, the implementation of the covid-19 vaccination in Indonesia has not been optimal due to factors; lack of public participation due to doubts about the "halal" status of vaccines, doubts about vaccine safety and effectiveness and fear of vaccine side effects. Conclusion: the implementation of vaccination that is not optimal based on reporting and constraints needs to be monitored and evaluated continuously from the central level to the community both in terms of policy, human resource support, information dissemination so that improvements can be made immediately in order to achieve the success of the vaccination program. Keywords: covid-19 vaccination, policy, implementation, success, vaccination constraints